Clinical features of atypical depression in bipolar and recurrent affective disorders, psychogenic depression - N. A. Tyuvina; M. S. Verbitskaya; G. I. Krenkel; E. N. Efremova (Неврология, нейропсихиатрия, психосоматика, 2022)
Objective: to perform a comparative study of the clinical features of atypical depression (AtD) in affective disorders of various origins: in bipolar affective disorder (BAD), recurrent depressive disorder (RDR) and psychogenic depression (PD).Patients and methods. A sample of 250 depressed patients aged 18 to 65 years were examined, of which 77 participants (50 women and 27 men) with symptoms of AtD were included to the study. Group 1 included 35 patients with BAD, group 2 – 18 patients with RDR, and group 3 – 24 patients with diagnoses including PD. The patients' condition was assessed using the diagnostic criteria for affective disorders according to ICD-10 and DSM-5 with a Montgomery-Asberg Depression Rating Scale (MADRS).Results and discussion. AtD detection rate was 30.8%, including 45.4% in BAD, 23.4% – in RDR, and 31.2% – in PD. AtD manifested at the age of about 20 years, and was more common in women. AtD in BAD occurred more often in individuals with cycloid, hyperthymic, and hysterical features. Affective fluctuations before the disease onset, a significantly greater number of depressive episodes in history were characteristic. The most frequent typical depressive symptoms included: daily and seasonal mood fluctuations, morning deterioration of well-being, decreased appetite. High comorbidity with metabolic endocrine diseases was observed. AtD in RDR often began spontaneously in individuals with emotionally labile, psychasthenic, and hysterical features. The most common typical depressive symptoms included melancholy, derealization, weakness, ideas of self-accusation, suicidal thoughts and attempts. A high comorbidity with cardiovascular diseases was found. AtD in PD occurred more often in psychasthenic individuals. The most characteristic symptoms included: increased appetite, anxiety, asthenia, superficial night sleep, hypochondriacal inclusions. Comorbidity with skin and gastrointestinal diseases was observed.Conclusion. The identified features of the clinical picture and course of AtD in BAD, RDR, and PD can be used for earlier and more accurate evaluation of affective disorders and the adequate treatment administration.